Microtomographic, histomorphometric, and molecular features show a normal alveolar bone healing process in iNOS-deficient mice along a compensatory upregulation of eNOS and nNOS isoforms - Carolina Fávaro FRANCISCONI; Priscila Maria COLAVITE; Angélica Cristina FONSECA; Michelle de Campos Soriani AZEVEDO; André Petenuci TABANEZ; Jéssica Lima MELCHIADES; Andreia Espíndola VIEIRA; Carlos Eduardo Palanch REPEKE; Marcela CLAUDINO; Gustavo Pompermaier GARLET (University of São Paulo, 2023)
Abstract Inducible nitric oxide synthase (iNOS) is one of the enzymes responsible for the synthesis of nitric oxide (NO), which is an important signaling molecule with effects on blood vessels, leukocytes, and bone cells. However, the role of iNOS in alveolar bone healing remains unclear. This study investigated the role of iNOS in alveolar bone healing after tooth extraction in mice. Methodology C57Bl/6 wild type (WT) and iNOS genetically deficient (iNOS-KO) mice were subjected to upper incision tooth extraction, and alveolar bone healing was evaluated by micro-computed tomography (μCT) and histological/histomorphometric, birefringence, and molecular methods. Results The expression of iNOS had very low control conditions, whereas a significant increase is observed in healing sites of WT mice, where iNOS mRNA levels peak at 7d time point, followed by a relative decrease at 14d and 21d. Regarding bone healing, both WT and iNOS-KO groups showed the usual phases characterized by the presence of clots, granulation tissue development along the inflammatory cell infiltration, angiogenesis, proliferation of fibroblasts and extracellular matrix synthesis, bone neoformation, and remodeling. The overall micro-computed tomography and histomorphometric and birefringence analyses showed similar bone healing readouts when WT and iNOS-KO strains are compared. Likewise, Real-Time PCR array analysis shows an overall similar gene expression pattern (including bone formation, bone resorption, and inflammatory and immunological markers) in healing sites of WT and iNOS-KO mice. Moreover, molecular analysis shows that nNOS and eNOS were significantly upregulated in the iNOS-KO group, suggesting that other NOS isoforms could compensate the absence of iNOS. Conclusion The absence of iNOS does not result in a significant modulation of bone healing readouts in iNOS-KO mice. The upregulation of nNOS and eNOS may compensate iNOS absence, explaining the similar bone healing outcome in WT and iNOS-KO strains.